SYNDROMIC AND NON-SYNDROMIC DEAFNESS, MOLECULAR ASPECTS OF PENDRED SYNDROME AND ITS REPORTED MUTATIONS - Shaukat, Shahzad; Fatima, Zareen; Zehra, Uruj; Waqar, Ahmed Bilal (Journal of Ayub Medical College Abbottabad, 2003)
Deafness means partial or complete hearing impairment and is one of the most prevalent sensory defects in humans. It can be due to genetic or environmental causes or a combination of both and may be Syndromic (associated with additional clinical features) or nonsyndromic (no other recognizable abnormal associated phenotype). The overall impact of hearing impairment is greatly influenced by the severity of hearing defect and by the age of onset. If defect is severe and presents in early childhood, it has dramatic effect on speech acquisition and thereby cognitive and psychosocial development. The mutations shown in the paper results in the conformational changes of protein and influence the phenotype of the affected individuals. For recessive cases of deafness it is possible to reduce the incidence of deafness by carrier screening in the families with multiple affected individuals and genetic counselling. Pendred Syndrome can be characterized by the triad composed of familial goitre, abnormal perchlorate discharge and congenital deafness.